Field Partitioning: The Emergence, Development and Consolidation of Subfields. Issue 7 (July 2021) - Faulconbridge, James; Muzio, Daniel
This paper develops the concept of the subfield as a key feature of field-level change. In particular, it analyses how a subfield emerges, develops and consolidates itself over time. It does this through the concept of field partitioning whereby a formerly established field generates a distinct subfield with its own institutional infrastructure. Three mechanisms are identified (focusing on new opportunities; inter-organization studies and intra-subfield networking; and distinction) through which field partitioning occurs. Each mechanism is shown to contribute to the development of specific aspects of the subfield's institutional infrastructure, as part of a dynamic process that differentiates the subfield from its parent field.